TAVI pilot outcomes: A South African healthcare funder perspective - Miot, J.; Moore, R.; Bhimsan, N.; Cornejo, S. (SA Heart Journal, 2017)
BACKGROUND: TAVI (Transcatheter aortic valve implantation) is used to replace the aortic valve in the treatment of aortic stenosis in high-risk, elderly patients who are unable to undergo conventional surgical replacement of the aortic valve (SAVR). However, concerns remain regarding the costs, long-term outcomes and safety of the device. A registry was developed by a healthcare funder to assess utilisation, outcomes and cost of this procedure in their patient population. METHODS: Registry data was collected for a period of 17 months. Clinical entry criteria included high-risk, elderly patients with symptomatic, severe aortic valve disease who were unsuitable for surgical valve replacement. Clinical outcomes were mortality, readmission and pacemaker requirements post-surgery. Primary outcome measure was all-cause mortality at 30 days. RESULTS: A cohort of 78 patients was enrolled, mean age of 79.53 years. Procedures were performed in 7 centers around the country. Thirty day all-cause mortality was 9 (11.54%) with 5 deaths occurring on the day of the procedure. Eighteen (23.1%) patients were readmitted within 30 days. Average LOS was 5.71 (±4.06SD) days with an average cost of ZAR327 962 per patient. CONCLUSION: Results suggest outcomes are similar to other settings and countries. Ongoing data collection is required to better understand long-term outcomes and costs.